Understanding Maternal Health with special signifcance to Antenatal Care: A Micro Level Study of Village Khagawal, District Chandauli, UttarPradesh - Sumedha; Singh, Suman (National Geographical Journal of India, 2022)
India has signicantly improved the Maternal Mortality Rate (MMR). With the beginning of twenty rst century an increasing trend in institutional deliveries and decreasing trend in deaths owning to complications during births has reduced MMR to an extent. Most commendable improvements have been recorded by the straggling Empowered Action Group (EAG) states, Uttar Pradesh (U.P.) being one of them. Still a long road is ahead. Inspite of governmental efforts in the form of various schemes, incentives and policies, Antenatal Care (ANC) coverage is still not universal and MMR remains high. The given study is designed to explore the prevailing situation of maternal health, particularly ANC in a small village in rural eastern U.P. In-depth interviews were conducted through Interview schedules along with Intense Focus Group Discussions (FGD's). Majority of the respondents availed at least one ANC visit with education being the major determinant affecting the utilisation of ANC. Average spacing between childbirth was two years. Women, who were in their 20s or 30s were more aware about the benets of ANC rather than their older counterparts. In brief, it was assessed that although, the situation is improving still there is scope for much improvement if the dream of universal ANC coverage is to be realized in turn making pregnancy and motherhood safer and comfortable.